KNOWLEDGE, ATTITUDES AND PRACTICES OF MOTHERS TOWARDS CHILDHOOD VACCINATION IN LAGOS STATE, NIGERIA - Idowu TO; Obohwemu KO; Iyevhobu KO (International Journal of Medical Science and Public Health Research, 2024)
Despite the significant impact of vaccination on reducing child mortality from vaccine-preventable diseases like measles, polio, tuberculosis, and haemophilus influenza, vaccine uptake and coverage remain a challenge, particularly in countries like Nigeria. While the government provides free routine immunization up to age two, many children miss out on essential vaccines beyond this age due to various factors. This study aimed to investigate the awareness, attitudes, and practices of mothers regarding childhood immunization, particularly beyond the age of two, in Alimosho Local Government Area of Lagos, Nigeria. A cross-sectional study was conducted with 291 mothers, collecting data on immunization awareness, attitudes, and practices using a modified, pretested questionnaire administered through an online survey. Descriptive and inferential Chi-square statistics were used to analyze the data. The results revealed that the majority of participants were Yoruba (77.3%), semi-employed (53.6%), and had tertiary education (92.1%). Although 76.6% of the women demonstrated poor knowledge of immunization, a significant majority (79.4%) had positive attitudes towards vaccination. While no significant association was found between socio-demographic variables and knowledge about immunization, ethnicity (p = 0.026), employment status (p = 0.016), and educational level (p < 0.001) were strongly associated with positive attitudes towards immunization. The overall knowledge and attitudes of mothers in Alimosho Local Government Area were found to be lower than reported in other regions of Nigeria. To address these findings, it is recommended that targeted health promotion strategies be developed to improve knowledge and awareness about immunization among mothers in this area. These strategies should leverage various media platforms to reach a wider audience and emphasize the importance of completing the full immunization schedule for children. Additionally, efforts should be made to enhance access to immunization services and address socio-demographic disparities that may influence vaccine uptake.